Differential diagnosis of lymphadenopathy - N. Govedarović, Nenad; R. Babić, Rade (Medical Word, 2021)
The majority of patients presenting with peripheral lymphadenopathy have easily identifiable causes that are benign or self-limited. Among primary care patients presenting with lymphadenopathy, the prevalence of malignancy has been estimated to be as low as 1.1 %. The critical challenge for the primary care physician is to identify which cases are secondary to malignancies or other serious conditions. Key risk factors for malignancy include older age, firm, fixed nodal character, duration of greater than two weeks, and supraclavicular location. Knowledge of these risk factors is critical to determining the management of unexplained lymphadenopathy. In addition, a complete exposure history, review of associated symptoms, and a thorough regional examination help determine whether lymphadenopathy is of benign or malignant origin. Unexplained lymphadenopathy without signs or symptoms of serious disease or malignancy can be observed for one month, after which specific testing or biopsy should be performed. While modern hematopathologic technologies have improved the diagnostic yields of fine-needle aspiration, excisional biopsy remains the initial diagnostic procedure of choice.